THE EFFECTS OF JIGSAW TYPE COOPERATIVE LEARNING MODEL AND EARLY STUDENT ABILITY ON AFFECTIVE ABILITY BIOLOGY OF CLASS XI IPA STUDENTS OF SMAN 1 BONJOL IN EDUCATION YEAR 2015/2016 - Ennike Gusti Rahmi (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2018)
Based on the results of observations that researchers do in SMAN 1 Bonjol Pasaman district on April 21, 2014, the fact in the biology learning process has not run in accordance with expectations, where the implementation of learning is still focused on the teacher as a source of information. In addition, students are less motivated, less active in following the lesson because of the lack of interaction of students with teachers or students with students. This is because teachers provide learning materials using only lecture methods. Students just listen and record what the teacher explains so that students are less understanding of the material. If there is a teacher who asks only one or two students who answered and others prefer silence. Students who want to ask or answer teacher questions are only high-ability students, while low-ability students do not want to be actively involved in learning. The low affective ability of students is also determined by the initial knowledge of the students, The aim of this study was to comprehend effects of jigsaw cooperative learning model and early ability on affective ability in biology of class XI IPA students in education year 2015/2016. This quasi experiment studey used 2 x 2 factorial study design. Sampling technique used was purposive sampling, resulting in class XI IPA4 as experiment, and class XI IPA3 as control groups. The instrument used is the affective aspect score sheet. The study results showed that there was an effect of jigsaw cooperative study model on student’s affective ability, of those with high or low early ebilities.